Exploring the electronic and photocatalytic properties of organic-inorganic hybrid polyoxometalates - Kibler, Alexander J. (2020)
This thesis encompasses the synthesis and characterisation of electro- and photoactive organic-inorganic hybrid polyoxometalates (POMs). Specifically, the use of aromatic organic groups, either as countercations (Class I), as covalently grafted moieties (Class II) or combination thereof, have been explored with regards to their abilities to fine-tune the inherent properties of the POM cluster. The ability to tune the properties of redox and photo-active polyoxometalates represents an important step in the formation of “designer” materials, where the physical and electronic properties of the system can be tailored towards bespoke applications. In Chapter 2, the combination of redox rich Wells-Dawson phosphotungstates with fluorescent dye-type π-extended benzathiadiazole (BTD) cations yield a family of Class I hybrids with different modes of quaternization (proton, methyl, acetic acid). Crystallographic studies on the protonated derivative showed that the planar BTDImH structure is perturbed by hydrogen bonding to the POM and the solvent. Measurements of the electronic properties of the materials in the solution and solid state revealed stark differences, suggesting that the properties of the material are a product of interactions between the two components in the solid state. It also demonstrated that the different quaternisation strategies resulted in different electrochemical behaviour due to the different protic environments provided. Finally, preliminary studies on the hybrid featuring BTDImH cations revealed that the compound is capable of acting as a carbon dioxide photoreduction catalyst, whereas the respective components showed no activity, testament to the synergic effects gained when the photoactive components are combined. Chapter 3 explores a new strategy for the covalent functionalisation of the Wells-Dawson phosphotungstate anion through the use of arylarsonic acids (Class II hybrids). Three different arylarsonic acids were explored bearing electron withdrawing (NO2), electron donating (NH2) and “neutral” (H) substituents in the para- position. Akin to their phenylphosphorus analogues, the arylarsonic hybrids were reduced at more positive potentials than the parent anion, and the redox potentials were tuneable based on the electronic nature of the rings. The perceived trends in the lowering of the LUMO energies was corroborated with DFT. The phenylarsonic hybrid was compared to phenylphosphonic and phenylsiloxane hybrids for the photoreduction of DMF with both UV-vis and visible light. The phenylarsonic hybrid was photosensitised towards visible light, and whilst the phenylphosphonic hybrid was more easily reduced, the phenylarsonic was more easily reoxidised with molecular oxygen. In Chapter 4, a combined approach is adopted in the synthesis of covalently functionalised polyoxometalate ionic liquids (POM-ILs) based on the Keggin anion. This work used the bulky trihexyltetradecylphosphonium cation (THTP) to generate ionic liquids from two covalently functionalised Keggins featuring phenylphosphonic and phenylsiloxane groups (Class I/II hybrids). Thermophysical techniques determined that the POM-ILs exhibited higher stability than their classical salt precursors and had a wider liquid range than the plenary POM-IL analogue, despite their physical similarities, the POM-ILs gave contrasting electrochemical properties due to the different nature of the linker atoms used to graft the phenyl ring to the POM. Remarkably, the phenylphosphonic derivative which is highly unstable as a classical salt showed drastic improvement in both its thermal and electrochemical stability due to the shrink-wrapping effect of the bulky cations.